PENILAIAN KERENTANAN BANGUNAN DI KABUPATEN MANOKWARI SELATAN AKIBAT GEMPA BUMI - Yoga Charol Vincenthius Tethool; Indra Birawaputra; Mayang K. F. Putri; Natalia E. Safkaur; Veronika Y. Ohoilulin; Geraldo R. Rombe (Construction and Material Journal, 2021)
Earthquake is a natural occurrence in which energy is released and propagated from the earth to the ground surface. The effects of the earthquakes include failure of building, landslides, tsunamis and so on. Mitigation actions are required to reduce the number of people killed or injured as a result of earthquakes. Assessing the vulnerability of buildings to earthquakes is one of the mitigation efforts. The Hazus Method is used to assess the vulnerability of a building. This method requires information such as: building typology and seismic activity at the location to be studied. The goal of this study is to assess the level of earthquake susceptibility based on the structure type in Manokwari Selatan Regency. Concludingly, the building typology in Manokwari Selatan Regency will be divided into five categories of vulnerability, specifically: no damage, light damage, moderate damage, major damage, and collapse. Based on observations, there are several typologies of the existing buildings in the Manokwari Selatan Regency, namely: wooden light frames (W1), Steel Moment Frame (S1L), Concrete Moment Frame C1L) and Reinforced Masonry Bearing (RM1L). The results of the analysis show that the typology Steel Moment Frame (S1L) has the possibility of light, moderate, heavy damage, collapse and no damage, respectively 7.13%, 32.66%, 39%, 18.13%, and 3.07%; the typology Concrete Moment Frame (C1L) are 8.39%, 34.91%, 36.84%, 16.35%, and 3.51% respectively; the typology wooden light frames (W1) are 18.16%, 47.89%, 21.18%, 10.03%, and 2.74%; the typology Reinforced Masonry Bearing (RM1L) has a probability of 10.76%, 34.45%, 36.06%, 13.14%, and 5.59%. Keywords: Earthquake, Building Typology, Building Vulnerability, Hazus Method.